1996
DOI: 10.1097/00007890-199612270-00017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Donor and Recipient Gender on the Outcome of Liver Transplantation12

Abstract: The decreased graft survival rate in male recipients of female livers warrants further study and may argue for modifying the current management of adult male liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…Although an association between female donors and negative postoperative outcome has been shown in some studies [55][58], we did not identify this correlation in our patient collective. Brooks, et al .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although an association between female donors and negative postoperative outcome has been shown in some studies [55][58], we did not identify this correlation in our patient collective. Brooks, et al .…”
Section: Discussioncontrasting
confidence: 62%
“…Brooks, et al . reported a decreased chance of survival when female livers were transplanted into male recipients [55]. Animal studies have revealed that estrogens have a biological influence on the long term postoperative outcome [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CIT and preservation solution, many other donor and recipient factors have been hypothesized as contributing to poor outcomes [4], [5], [8], [9], [38], [50], [51], [52], [53], [54], [55]. Being able to use a simple blood test or patient historical factor to predict outcome prior to transplant has obvious advantages for making organ allocation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Organ Procurement and Transplantation Network and the Scientific Registry of Transplant Recipients, has recently has begun to publish the effect of cold-ischemia time (the time from clamping of the donor aorta until the anastomosis of the organ to the recipients vascular system or the organs disposal) on clinical outcomes- patient and graft survival [1]. Many other factors also contribute to the success or failure of an organ to function [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12] once transplanted and on patient and graft survival. However, cold-ischemia time also determines in part how far we can transport organs [13].…”
Section: Introductionmentioning
confidence: 99%
“…The donor's gender does not affect survival or outcome after liver transplantation [4,47]. Some older studies proposed that female livers have a lower survival and that a gender mismatch leads to higher graft failure; however, more recent studies could not support the assumed outcome differences related to donor gender [4,15,33,35,47,48,49,50,51,52]. During follow-up, no gender-related differences are being observed in the incidence of malignancies or rejections; however, more women develop renal dysfunction after liver transplantation [15,23,50,51,52,53,54,55].…”
Section: Liver Transplantationmentioning
confidence: 99%